2009
DOI: 10.1093/eurheartj/ehp480
|View full text |Cite
|
Sign up to set email alerts
|

An optical coherence tomography study of a biodegradable vs. durable polymer-coated limus-eluting stent: a LEADERS trial sub-study

Abstract: Strut coverage at an average follow-up of 9 months appears to be more complete in patients allocated to BESs when compared with SESs. The impact of this difference on clinical outcome and, in particular, on the risk of late stent thrombosis is yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
157
5
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(174 citation statements)
references
References 24 publications
5
157
5
7
Order By: Relevance
“…Given this background, BP-DES may represent an attractive solution for patients with STEMI, as complete polymer biodegradation after drug elution is expected to result in a vessel wallstent interaction resembling that seen after bare metal stenting. Intravascular imaging studies have shown encouraging data regarding vessel healing following biodegradable polymer DES implantation in man 27,28 . Moreover, in a broadly inclusive patient cohort, BP-DES demonstrated a reduction in clinically indicated target lesion revascularisation and very late definite stent thrombosis up to four years in comparison to durable polymer SES 12 , an effect potentially magnified in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Given this background, BP-DES may represent an attractive solution for patients with STEMI, as complete polymer biodegradation after drug elution is expected to result in a vessel wallstent interaction resembling that seen after bare metal stenting. Intravascular imaging studies have shown encouraging data regarding vessel healing following biodegradable polymer DES implantation in man 27,28 . Moreover, in a broadly inclusive patient cohort, BP-DES demonstrated a reduction in clinically indicated target lesion revascularisation and very late definite stent thrombosis up to four years in comparison to durable polymer SES 12 , an effect potentially magnified in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, optical coherence tomography (OCT) showed better midterm intravascular findings for the biodegradable polymer BES compared to that of the durable polymer SES, suggesting BES had improved biocompatibility. 3,4) However, BES did not exhibit angiographic efficacy compared to SES in 2 previous randomized studies. 7,8) Compared to the results of the Nobori-Japan trial (0.14 mm), 7) the mean LLL in the SES group (0.28-0.36 mm; Tables III and IV) was larger, suggesting that the present cohort included complex lesions with a higher propensity for ISR, reflecting the daily practice environment as described above.…”
Section: Discussionmentioning
confidence: 79%
“…1,2) The biolimus-eluting stent (BES; Nobori) also showed a better midterm intravascular response compared to SES, owing to its properties such as being a biodegradable polymer and the highest lipophilicity among the limus analogues. 3,4) However, despite these advanced aspects of EES and BES compared with the former evidence-based first generation "-limus" DES, that is, SES, prospective randomized trials have not demonstrated significantly better midterm angiographic outcomes for either EES 5,6) or BES 7,8) in terms of binary in-stent restenosis, TLR, or mean magnitude of in-stent late luminal loss compared to those of SES.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that new-generation biolimus-eluting stents had better strut coverage at 9 months by OCT than sirolimus-eluting stents [1], but were not associated with a clear improvement in stent thrombosis after 2 years [2]. Conversely, newgeneration zotarolimus-eluting stents had similar 13-month OCT findings compared to new-generation everolimus stents [3], but tended to have more definite thrombotic events at 12 months [4].…”
mentioning
confidence: 92%